Extreme lunch : life and death in the food chain - Piper, Ross. (Mankato, Minn. : Capstone Press, 2008)
Presents various plants and animals and explains their role in the food chain, including how adaptations help them survive.
Includes bibliographical references (p. 31) and index.
4.9
3-6
Keywords: Food chains (Ecology) -- Juvenile literature; Food chains (Ecology); Food chains (Ecology)